"Barcelona or Die": Understanding Illegal Migration from Senegal - Linguère Mously Mbaye (Institute for the Study of Labor (IZA), 2013)
Fatalities from illegal immigration from Africa is an important issue, representing a major challenge for both major migrant sending and receiving countries. Nonetheless, almost nothing is known about how the illegal migration intentions of potential migrants are formed. This paper aims to explain the factors behind the formation of these intentions to migrate illegally by using an original survey among urban Senegalese individuals. Remarkably, the results show that potential illegal migrants are willing to accept a substantial risk of death (25% at the median). Furthermore, the paper also finds that the price of illegal migration, migrant networks and high expectations play important roles in the decision to illegally migrate. Moreover, I find that, contrary to conventional thinking, stricter immigration policies deter potential legal migrants more than potential illegal migrants.
Keywords: F22; O15; 330; illegal migration; intentions; Senegal